Senyawa Bioaktif Bioinsektisida Daun Sirsak (Annona mucirata) dan Pengaruhnya terhadap Keanekaragaman Artropoda pada Tanaman Padi (Oryza sativa L.) - Syarief, Mochamad; Fajar Setyabudi, Ibnu; Erdiyansyah, Iqbal (JURNAL AGROPLANT, 2023)
The aim of the study was to determine the content of bioactive compounds in soursop leaf bioinsecticides and their effect on the diversity of arthropods in rice. This research began from July to October 2022 at the Plant Protection Laboratory and Bioscience Laboratory of the Jember State Polytechnic and Rice Cultivation Land in Balung Lor Village, Balung District, Jember Regency. Arthropod samples were observed visually using Sweep Net Trap, Yellow Pan Trap, Sticky Trap and Pitfall Trap. The GCMS test results detected 29 compounds in soursop leaves.   The highest compounds as repellent and antifeedant detected were palmitic acid, oleic acid and acetic acid at 18.39%, 17.40%, 13.83%. The result of probit analysis of LC95 toxicity was 28.92%. The number of individuals in the bioinsecticide treatment was 2036 individuals, 32 species consisting of: 10 herbivores,   13 predators, 3 parasitoids, 4 pollinators, and 3 detrivores. Fipronil numbered 1198 individuals, 26 species consisting of: 10 herbivores, 10 predators, 2 parasitoids,  3 pollinators, and 1 detrivore. Diversity index (H`) shows moderate category in both treatments, dominance index (C`) does not show dominance in both treatments, species richness index (R) in both treatments is moderate, species evenness index (E) is evenly distributed in both treatments and Sorensen   The Similarity Index (ISS) is classified as the same with a value of 89.66%. The yield of dry grain in the soursop leaf bioinsecticide treatment was higher (38.25 g per clump) than Fipronil 33.29 gr per clump.